POLICY AND SERVICES FOR STUDENTS WITH DISABILITIES: MATTERS ON STUDENT AFFAIRS (Jurnal Pembangunan Sosial, 2022)
The inclusivity of students with disabilities into the mainstream education is getting more attention when all institutions of higherlearning, public and private, are expected to implement the disability inclusion policy. Universiti Utara Malaysia (UUM) has beensupporting the potential of students with disabilities by offering academic programmes. This study examines the policy regardinginclusivity for people/students with disabilities and services provided. Using a qualitative approach, the primary data were obtained through the interviews with the officer of Student Affairs Department (HEP) and three disabled students. Responses were recorded, transcribed and analysed using thematic approach. HEP was selected since the Department involves with students affairs and provides services for students with disabilities. A focus group discussion was held with the three students, taking different programmes, and having different type of impairments. The study found that: (a) UUM has adopted the PWD Guideline by the Ministry of Education; (b) UUM supports the inclusivity education when students with disabilities are offered to enrol into the academic programmes; and (c) services offered for students with disabilities are limited. It is recommended for the institution to have a written disability policy that suitable with the surrounding and environment of the campus and education. At the same time, its true implementation is essential along with the application of the social model in materialising the inclusivity concept.